2018
DOI: 10.1039/c7ra10421a
|View full text |Cite
|
Sign up to set email alerts
|

Sorption characteristics ofN-acyl homserine lactones as signal molecules in natural soils based on the analysis of kinetics and isotherms

Abstract: Sorption characteristics of N-acyl homoserine lactones (signal molecules) in natural soils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…AHLs consist of fivemembered homoserine lactone (HSL) rings containing varied amide-linked side chains. Sorption and hydrolysis of AHLs are two processes that influence the bioavailability and activity of AHLs in natural environments such as soil, resulting in quorum quenching (Grandclement et al 2016;Sheng et al 2018). Sorption of AHLs varied with biochars with different structures.…”
Section: Biochar-microbe Interactionsmentioning
confidence: 99%
“…AHLs consist of fivemembered homoserine lactone (HSL) rings containing varied amide-linked side chains. Sorption and hydrolysis of AHLs are two processes that influence the bioavailability and activity of AHLs in natural environments such as soil, resulting in quorum quenching (Grandclement et al 2016;Sheng et al 2018). Sorption of AHLs varied with biochars with different structures.…”
Section: Biochar-microbe Interactionsmentioning
confidence: 99%
“…Prior studies have shown that AHLs can sorb onto some soils (Cheng et al, 2018; Sheng et al, 2018), but it is not known how soil mineral composition affects signal sorption. We hypothesized that differences in mineral surface area will impact the amount of AHL being sorb into the matrices, thereby changing microbial perception of this signal.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that both diffusion and intraparticle diffusion processes took place simultaneously during the adsorption of the dyes. Moreover, the multilinearity demonstrated that the adsorption was not only controlled by intraparticle diffusion [ 45 ]. Further, to predict the actual rate-controlling step involved in the adsorption process, we applied the Boyd kinetic model.…”
Section: Resultsmentioning
confidence: 99%
“…Further, to predict the actual rate-controlling step involved in the adsorption process, we applied the Boyd kinetic model. As shown in Figure S1 , the plot of the Boyd model does not pass through the origin, suggesting that the diffusion process might be the rate-controlling step of the adsorption process [ 45 ].…”
Section: Resultsmentioning
confidence: 99%